Aproximaciones a las audiencias comunitarias de una radio indígena: el caso de La Voz de la CONFENIAE (Dossier: Comunicación comunitaria, mediaciones digitales y soberanía tecnológica) - Benavides Morales, Ana Cristina (2026)
The Ecuadorian indigenous movement has played a central role in the political sphere of the last century, its main demand revolves around the construction of a plurinational state, and for this purpose it uses different platforms for visibility, collective action repertoires and political advocacy disseminated by its own media. Since 2009, a new regulatory framework opened the way for the allocation of radio and television frequencies for indigenous peoples, nationalities and organizations, the indigenous media, in addition to building participatory audiences and news consumers, broadcast artistic representations of nationalities, and become legitimate spokespersons while reaffirming community, identity and organizational values. The research presented here studies the case of Radio La Voz de la Confederación de las Nacionalidades Indígenas de la Amazonía Ecuatoriana as a mediator of communal commitment. In its pilot phase, it identified and analyzed the audiences through a survey applied in the Unión Base Community located in the Province of Pastaza, where the radio station is based, as well as interviews with its actors. The main results explain the relationship of La Voz’s audiences with the contents, programming grid, level of two-way participation, and the social role of the media in the community life of the organization.